Focussed assessment of certain existing maximum residues levels of concern for abamectin - European Food Safety Authority (EFSA) (Wiley, 2021)
Abstract In compliance with Article 43 of Regulation (EC) No 396/2005, the European Food Safety Authority (EFSA) received from the European Commission a mandate to provide its reasoned opinion on the existing maximum residue levels (MRLs) for abamectin which might lead to consumers intake concerns on the basis of the lower toxicological reference values established during the peer review, the data currently available to EFSA and the outcome of the Member States’ consultation. To identify the MRLs of potential concern that require a more detailed assessment, EFSA screened the existing MRLs for abamectin considering the new toxicological reference values and an acute risk could not be excluded for 12 commodities. Fall‐back MRLs for nine commodities were proposed based on the data received under the present assessment. For apples, pears and escaroles, fall‐back MRLs could not be derived, and thus, a lowering of the MRLs for these crops to the limit of quantification (LOQ) is proposed.